2021
DOI: 10.1002/mar.21557
|View full text |Cite
|
Sign up to set email alerts
|

How scarcity and thinking styles boost referral effectiveness

Abstract: Referral reward programs (RRPs) are a widely used tool to stimulate word-of-mouth (WOM). However, marketers still face a dilemma-while incentivization encourages senders to make referrals, recipients often react negatively towards such incentives.We propose a solution-referral scarcity-to improve referral effectiveness depending on thinking style. Three experiments show that limiting the number of referral rewards makes holistic-thinking recipients feel more special, boosting their referral acceptance and RRP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Past research has highlighted that consumers view scarcity favorably and buy products when they are perceived as scarce (Ang et al, 2021 ; Chen et al, 2020 ; John et al, 2018 ). We document that in the service firm context, “scarce is good” heuristic is most applicable when service firms experience both scarcity of money resource as well as time resource since firms that are both poor and busy have greater purchase preference compared to firms that are only poor or only busy.…”
Section: Discussionmentioning
confidence: 99%
“…Past research has highlighted that consumers view scarcity favorably and buy products when they are perceived as scarce (Ang et al, 2021 ; Chen et al, 2020 ; John et al, 2018 ). We document that in the service firm context, “scarce is good” heuristic is most applicable when service firms experience both scarcity of money resource as well as time resource since firms that are both poor and busy have greater purchase preference compared to firms that are only poor or only busy.…”
Section: Discussionmentioning
confidence: 99%
“…Nisbett et al (2001) proposed the analytic‐holistic framework which stipulates that an individual's environment promotes certain cognitive processes more than others. This framework was originally developed to provide an explanation for cultural differences; however, recent research acknowledges within‐culture individual differences in analytic and holistic thinking (Ang et al, 2021; Choi et al, 2007; Meng & Chan, 2022). Nisbett et al (2001, p. 293) defined holistic thinking as “involving an orientation to the context or field as a whole, including attention to relationships between a focal object and the field, and a preference for explaining and predicting events on the basis of such relationships.” In contrast, analytic thinking “involves a detachment of the object from its context, a tendency to focus on attributes of the object to assign it to categories, and a preference for using rules about the categories to explain and predict the object's behavior.”…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Observing the consumption behavior of individuals under scarcity using eye-tracking technology, results show that individuals spend more time on price-related information and less time on other information (Zhao & Tomm, 2017;Mullainathan & Shafir, 2013). More importantly, research has shown that individuals' cognitive load increases under scarcity, leading them to rely more on heuristic processing when making decisions (Ang et al, 2021). Additionally, there is direct evidence that scarcity perception also affects individuals' perception of product quality (Lee et al, 2018).…”
Section: Moderating Role Of the Sense Of Scarcitymentioning
confidence: 99%